Effects of targeted knee flexion angle on the biomechanical factors of upward and downward phases during forward lunge - Lim, Y.-T.; Park, J. S.; Lee, J. W.; Kwon, M.-S. (Korean Journal of Sport Biomechanics, 2017)
Objective: The aim of this study was to investigate the effect of targeted knee flexion angle on biomechanical factors of knee joint between upward and downward phases during the forward lunge. Method: Eight elderly subjects (age: 22.23±1.51 years, weight: 69±6.63 kg, height: 174.88±6.85 cm) participated in this study. All reflective marker data and ground reaction force during a forward lunge were collected. The knee joint movement and reaction force and joint moment at maximum knee flexion angle were compared by repeated measures one-way analysis of variance (ANOVA) (p<.05). The peak knee joint reaction force and joint moment between upward and downward phases were compared by repeated measures two-way ANOVA (p<.05). Results: The anterior and vertical knee joint movements, reaction force, and extensor moment of 80° targeted knee flexion condition at maximum knee flexion angle was greater than both 90° and 100° conditions (p<.05). The 80° knee flexed angle condition had greater peak joint reaction force and extensor moment compared with both 90° and 100° conditions between upward and downward phases during the forward lunge. Conclusion: As the targeted knee joint flexion angle increases, knee joint movement and kinetic variables become greater during the forward lunge exercise.